2019
DOI: 10.1097/mat.0000000000000771
|View full text |Cite
|
Sign up to set email alerts
|

Cannula-Related Infection in Patients Supported by Peripheral ECMO: Clinical and Microbiological Characteristics

Abstract: Little is known about cannula-related infection (CRI) in patients supported by extracorporeal membrane oxygenation (ECMO). The aim of this study was to assess the incidence, the risk factors, prognosis, and microbiological characteristics of CRI in patients supported by ECMO. This retrospective cohort study was conducted in one intensive care unit (ICU). Among 220 consecutive patients with peripheral ECMO, 39 (17.7%) developed CRI. The incidence of CRI was 17.2 per 1,000 ECMO days. The main isolated microorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 18 publications
2
40
0
3
Order By: Relevance
“…Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is a temporary mechanical circulatory support that has been increasingly used over the last decade to restore and maintain adequate end-organ perfusion and improve outcomes in patients with refractory cardiogenic shock [1,2]. Nevertheless, the weaning of VA-ECMO should be daily questioned, as several studies reported severe complications like cannula-related infections [3], bleeding [4], and thromboembolic events [5] associated with prolonged VA-ECMO durations. Dobutamine is currently used to improve myocardial contractility during VA-ECMO, aiming to enhance left ventricular ejection and aortic valve opening and also to shorten ECMO duration.…”
Section: Introductionmentioning
confidence: 99%
“…Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is a temporary mechanical circulatory support that has been increasingly used over the last decade to restore and maintain adequate end-organ perfusion and improve outcomes in patients with refractory cardiogenic shock [1,2]. Nevertheless, the weaning of VA-ECMO should be daily questioned, as several studies reported severe complications like cannula-related infections [3], bleeding [4], and thromboembolic events [5] associated with prolonged VA-ECMO durations. Dobutamine is currently used to improve myocardial contractility during VA-ECMO, aiming to enhance left ventricular ejection and aortic valve opening and also to shorten ECMO duration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on one complication at a time (nosocomial infection, thromboembolic event, bleeding, transfusion, etc.) and on the relationship between this specific complication and death [ 1 3 , 8 , 9 , 23 , 24 ]. Our study used a large cohort and a methodology that allowed us to highlight: i ) complications that cluster together and cluster close to death; and ii ) four patterns of patients according to complications, including one with no complications.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent complications are hemorrhagic, thrombotic, and infectious events [ 3 7 ]. While previous studies have focused on the relationship between some of these complications and the risk of death, the relationship between different complications has never been specifically examined, despite the fact that the occurrence of one complication is known to favor the occurrence of others [ 1 3 , 8 , 9 ]. For example, hemorrhagic shock and/or blood transfusion can favor the occurrence of a bacterial infection and/or of a thrombotic event [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher yet, are the rates of nosocomial infections, with published incidence rates ranging from 8-64%. These account for blood stream or peripherally-inserted cannula infections, and ventilator associated pneumonia (VAP) (16)(17)(18)30). It is understandable that critically-ill patients with multiple invasive lines, ongoing mechanical ventilation, VA-ECMO circuit exposure to blood, and higher length of ICU stay, are at higher risk for developing an infection.…”
Section: Infection and Significant Inflammationmentioning
confidence: 99%
“…Studies have shown that the most common bloodstream pathogens identified in VA-ECMO-supported patients are Staphylococcus aureus and other staphylococcus organisms, accounting for up to 38% of all bacteremia cases (16)(17)(18). Just as in non-ECMO patients, VAP is a risk for patients supported on mechanical ventilation.…”
Section: Infection and Significant Inflammationmentioning
confidence: 99%